Blood Glucose, Cholesterol, Body Mass Index and Systemic Blood Pressure in Psychiatric Patients Attending a Tertiary Care Hospital of Sindh (Medical Forum Monthly, 2024)
Objective: The present observational study was conducted to determine the blood glucose, body mass index, blood pressure and serum cholesterol in psychiatric patients.Study Design: Observational study.Place and Duration of Study: This study was carried out at Psychiatric Clinic, Department of Medicine, Indus Medical College, Tando Muhammad Khan, Sindh from June 2014 to January 2016.Materials and Methods: A sample of 275 new cases suffering from different Psychiatric disorders was selected. Diagnosis of Psychiatric disorders was made by a consultant Psychiatrist. Body weight, height and systemic blood pressure were measured by standard methods. Willing participants were asked to sign a proforma of consent for ethical issues. Data was entered on excel sheet and copied to the SPSS 22.0 for statistical analysis. Analysis was performed at P value of ≤ 0.05.Results: Mean ± SD age was noted as 47± 11.97 years (p = 0.02). Male to female ratio was 1.83 vs. 1.0 (p=0.0001). BMI ≥ 30 was noted in 26.5% of subjects. Of 275 study subjects, normal blood glucose was noted in 79.6% while 20.3% of psychiatric patients showed raised blood glucose levels. Normal and raised blood cholesterol was noted in 65.09% and 34.9% respectively. Psychiatric disorders were correlated with blood glucose and blood cholesterol levels.Conclusion: Psychiatric disorders are a risk factor for raised blood glucose, blood cholesterol, BMI and Systemic hypertension; this predisposes patients for diabetes mellitus and associated morbidities.